(untitled) (Journal of Nepal Geological Society, 2000)
A catastrophic landslide occurred at midnight of 20 September 1988 at a small village of Darbang (1130 m above mean sea level) in western Nepal. The village is situated approximately 40 km northwest of the district capital Baglung. Farmhouses spread out on both sides of the Myagdi Khola, a main tributary of the Kali Gandalki River. An overly steep and more than 800 m high northern flank of a mountain collapsed spontaneously. Approximately 5 million m3 of the displaced material blocked the valley of the Myagdi Khola and dammed the river for 6 hours. The eventual breakup of the landslide dam caused extreme flooding in the lower reaches. Many houses of Darbang, particularly on the right bank of the Myagdi Khola, were destroyed. More than 100 persons lost their lives. This catastrophic event could be interpreted as a revisit of the devastating landslide of 1926, which killed more than 500 villagers. Diverse lithology (phyllites, schists, and quartzites), presence of the MCT in the vicinity, extremely high relief; and environmental degradation (e.g., deforestation), are regarded as the primary causative factors of the Darbang Landslide. Yet the decisive factor behind the massive landslide of 1988 was the unique meteorological situation of that year. The meteorological data show that, during the pre-monsoon months of April, May, and June 1988, the maximum temperature was 2° C higher than the average for the decade. Monthly precipitation measured in May and June of 1988 showed the totals respectively 37% and 24% below the decade-average. It led to extreme aridity in the period preceding the onset of the seasonal monsoons. Soils dried out and deep cracks were formed in this process. During the heavy summer rainfall of 1988 the cracks functioned as conduits of water. The bedrock contained numerous fractures and joints, through which the .vater seeped deep into it. Extremely heavy precipitation in August, with rainfall of up to 17% above the decade-average, aggravated this delicate situation. In the first half of September 1988 precipitation peaked. These meteorological conditions, coupled with the already saturated bedrock, and deteriorated natural vegetation lead to the collapse of the mountain flank. Primary causative factors and environmental degradation over a longer period were underlying reasons for the initial weakening of the site, but the unique weather situation in 1988 was the main trigger of this catastrophic event.